Efektivitas Penerapan Sistem Pengendalian Internal Berbasis Religius Magis pada Sistem Pemberian Kredit di LPD Desa Sudaji - Candra, Ketut David Alit; Purnamawati, I Gusti Ayu (Universitas Pendidikan Ganesha, 2021)
This study aimed to determine how was the effectiveness of magical religious-based internal control on credit provision in Sudaji Village LPD which this control aims to improve the credit system considering the frequent occurrence of events such as non performing loans in Sudaji’s Village LPD. This study will measure the effectiveness of internal controls used in Sudaji Village LPD. The data used in this study are primary data and secondary data with data collection methods using interviews, observation and documentation. The object of research is the Sudaji Village LPD and the informants of this study are from the management of the the sudaji village LPD. The techniques used in data analysis are data reduction, data presentation, data analysis and conclusion drawing. The conclusion of this study states that effectiveness of the implementation of internal control systems on lending in Sudaji Village LPD can provide convenience to prospective debtors or villagers who apply for loans or credit application.